2018
DOI: 10.1007/s00726-018-2611-x
|View full text |Cite
|
Sign up to set email alerts
|

High glycine concentration increases collagen synthesis by articular chondrocytes in vitro: acute glycine deficiency could be an important cause of osteoarthritis

Abstract: Collagen synthesis is severely diminished in osteoarthritis; thus, enhancing it may help the regeneration of cartilage. This requires large amounts of glycine, proline and lysine. Previous works of our group have shown that glycine is an essential amino acid, which must be present in the diet in large amounts to satisfy the demands for collagen synthesis. Other authors have shown that proline is conditionally essential. In this work we studied the effect of these amino acids on type II collagen synthesis. Bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 51 publications
(65 reference statements)
1
59
0
Order By: Relevance
“…This effect is likely not restricted to PDGF-AA but true for other stimulators of ECM protein formation such as TGFb1 4 thereby linking ECM protein synthesis to enhanced reliance on glycolysis. Increasing glycolytic flux and lactate production not only delivers ATP, but is also key for essential aspects of collagen formation such as glycine synthesis and collagen hydroxylation 4,67,68 . In contrast, cell proliferation was not dependent on glycolysis in agreement with previous studies 69 .…”
Section: Discussionmentioning
confidence: 99%
“…This effect is likely not restricted to PDGF-AA but true for other stimulators of ECM protein formation such as TGFb1 4 thereby linking ECM protein synthesis to enhanced reliance on glycolysis. Increasing glycolytic flux and lactate production not only delivers ATP, but is also key for essential aspects of collagen formation such as glycine synthesis and collagen hydroxylation 4,67,68 . In contrast, cell proliferation was not dependent on glycolysis in agreement with previous studies 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Although several lines of evidence suggest that Pro is conditionally essential amino acid that must be present in diet to support collagen biosynthesis, recent studies provided evidence that glycine is as well as important in diet to satisfy the demands for the process [56]. However, it has been found that milimolar concentration of glycine is required to enhance type II collagen in bovine chondrocytes, while Pro and lysine evoked the effect at physiological concentrations [56].…”
Section: Role Of Proline and Glutamine In Regulation Of Collagen Biosmentioning
confidence: 99%
“…Concentrations of glycine in GRS-derived acid whey were significantly higher than those from TMR, while concentrations were significantly higher in sweet whey derived from both pasture-based systems when compared to TMR. Glycine is a nonessential proteinogenic AA, primarily utilized in the synthesis of collagen, with limited function in the synthesis of other proteins and metabolic pathways [22]. Previous work by Meléndez-Hevia and de Paz-Lugo [23] suggests that a restriction in the stoichiometry of the glycine synthesis reaction may lead to insufficient glycine production relative to metabolic demand, making glycine an essential or conditionally essential AA.…”
Section: Total Amino Acid Compositionmentioning
confidence: 99%